Evaluation of Complex Antioxidant Systems and the Hormesis Effect of Radon in Experimental Studies on Rats of the Krushinsky-Molotk Line - Marine Nikolaishvili; Zaqaria Nanobashvili; Nodar Mitagvaria; Gvantsa Chkadua; Khatuna Dondoladze; Salome Omiadze; Sesili Beriashvili; Tamar Ordenidze; Mariam Nikuradze (Current Innovations in Medicine and Medical Science Vol. 6, 2022)
The current study is the first to attempt R-Ho inhalation for the treatment of epileptic seizures in animal models, with further translation to clinical trials in humans via a pilot phase II study. According to our findings, radon inhalation in experimental animals, particularly in genetically determined rats with epileptic seizures, altered all parameters of the epileptic seizure development picture, including the hidden period and the duration of the first and second wild jogs after the audiogenic signal. On the third day, there was no response to the audiogenic signal and not a single episode of tonic-clonic seizures. All of the above indicate that radon inhalation could be used to treat epilepsy. More profound and scientifically systematised approaches are required to determine the uniqueness of Tskhaltubo water springs, as well as extensive research into the mechanisms of radon effects on the excitatory and inhibitory functions of the CNS, as well as additional clinical studies to establish its effect on humans. However, based on the results of the experiment, it can be concluded that studies conducted on experimental animals have shown that the phenomenon of hormesis develops when water is inhaled from a water, which regulates oxidative processes in the brain by activating antioxidants, which is manifested by the reduction of existing epileptic seizures and is manifested in quantitative changes in activation, Na / K-ATPase and specific glutaminergic neurons of the "attack center" of the hypothalamus. Inhalation of Tskhaltubo water can be considered as a method of treatment with an anticonvulsant effect proven by experimental studies.